The genesis of Eocene granite‐related Lailishan tin deposit in western Yunnan, China: Constraints from geochronology, geochemistry, and S–Pb–H–O isotopes. (1st September 2020) - Wang, Weiqing; Dong, Guochen; Sun, Zhuanrong; Dong, Pengsheng; Pan, Yanning; Ketchaya, Yanick Blaise; Lemdjou, Yanick Brice; Geng, Jianzhen
Abstract : The Tengchong‐Lianghe tin metallogenic district in western Yunnan is an important tin mineralization area in the Sanjiang Tethyan Metallogenic Domain from southwestern China. The Lailishan deposit is one of the largest tin deposits in this district and spatially and temporally associated with Eocene granites. LA‐MC‐ICP‐MS cassiterite U–Pb dating (49.8 ± 2.6 Ma) suggests that the tin mineralization is coeval with the Lailishan granites. The contact between the monzogranite and the syenogranite is gradual and both are weakly peraluminous, with high SiO2, Al2 O3, and total alkali contents. They are characterized by negative Eu anomalies and the depletion in high‐field‐strength elements and enrichment in large‐ion lithophile elements. Compared with the monzogranite, the syenogranite is more evolved and exhibit 'tetrad effect'. The Lailishan monzogranite was probably derived from the partial melt of the ancient crustal basement from the Tengchong Block under syn‐collisional tectonic setting. The syenogranite was cogenetic with monzogranite and experienced the process of fractional crystallization. The mineralization process is divided into three successive mineralization stages (I–III) in this study. These stages are characterized by the coarse‐grained cassiterite and high temperatures (216–337°C), light brown or colourless cassiterite and moderate temperatures (160–243°C), and dark brown cassiterite and low temperatures (116–199°C) of ore‐forming fluids, respectively. From the Stage I to later stages, both the δ 18 OH2O and δDSMOW values of fluids are decreasing and shift from magmatic water towards meteoric water, indicating that the ore‐forming fluids derived from granitic melts and mixed over time with meteoric water with the decrease of temperature. The δ 34 S values of pyrites and pyrrhotites (2.4–5.9‰) and Pb isotopic compositions for pyrites from Lailishan deposit ( 206 Pb/ 204 Pb = 18.687–19.402) are similar with those of Lailishan granites. We propose that the Lailishant in deposit is derived from the Lailishan granites. Abstract : The δ34S values of pyrites and pyrrhotites from Lailishan deposit are within the range of the δ34S values of Lailishan granite, indicating a magmatic source. The magmatic fluids produced by the Lailishan granites are enriched in Sn. The exsolved magmatic fluids mixed with meteoric water and the Sn‐mineralization happened with the decreasing of temperature. The coarse‐grained cassiterite from Stage I precipitated at about 216 −337°C, with the crystallization of topaz, quartz, muscovite, and pyrite. As the temperature decrease to 160 −243°C, the light brown or colourless cassiterite, quartz, and pyrite from Stage II began to appear. Most of the cassiterites from Lailishan deposit were precipitated in these two stages. During the last stage, when the temperature was lower than 200°C, the fluids with low salinity yielded dark brown cassiterite, quartz, calcite, sericite, fluorite, and pyrite.